2011
DOI: 10.1080/10887156.2011.546191
|View full text |Cite
|
Sign up to set email alerts
|

Is high involvement at work and home so bad? Contrasting scarcity and expansionist perspectives.

Abstract: Using the scarcity and enhancement paradigms, this study examined whether high involvement in both work and home roles would be related to negative or positive outcomes for individuals. Data were collected from 356 working adults through an online survey. Work involvement and home involvement and their interaction were hypothesized to be related to time-, strain-, and behavior-based work-to-home and home-to-work conflict and positive affective and instrumental work-to-home and home-to-work spillover. Both work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Generally, work-related burn-out particularly accounts for individuals who have to fulfill both professional and parental responsibilities ( Kossek and Lautsch, 2012 ). These individuals are seriously facing the challenge of participating successfully both as employee and family member, since involvement in any role is associated with additional demands on working hours, time allocated to care for children, and time for household tasks ( Prottas and Hyland, 2011 ). Usually, not all demands can be fully met and the accumulation of roles may call upon an individual’s scarce resources, such as time, energy and commitment, and may enhance the experience of stress ( Hobfoll, 2001 ; Eby et al, 2005 ; Bakker and Demerouti, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, work-related burn-out particularly accounts for individuals who have to fulfill both professional and parental responsibilities ( Kossek and Lautsch, 2012 ). These individuals are seriously facing the challenge of participating successfully both as employee and family member, since involvement in any role is associated with additional demands on working hours, time allocated to care for children, and time for household tasks ( Prottas and Hyland, 2011 ). Usually, not all demands can be fully met and the accumulation of roles may call upon an individual’s scarce resources, such as time, energy and commitment, and may enhance the experience of stress ( Hobfoll, 2001 ; Eby et al, 2005 ; Bakker and Demerouti, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study with working adults, Protass and Hyland (2011) examined whether high involvement in both job and family roles was related to negative or positive outcomes for individuals. They found that both job and family involvement hold positive relationships with positive spillovers, while the interaction terms between job and family involvement were unrelated to the dependent variables (i.e., time-, strain-, and behavior-based job-to-family and family-to-job conflict and positive affective and instrumental job-to-family and family-to-job spillover).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Empirical research assessing positive spill over has made use of role enhancement theory (Grzywacz & Marks, 2000;Prottas & Hyland, 2011). Grzywacz and Marks (2000) found that lower posi tive spillover from family to work was related to less support from spouse and other family members among both men and women.…”
Section: Home To Work Spillover and Psychological Distress In Middle-mentioning
confidence: 99%
“…This situation may be especially true for individuals with family members who support their careers, making positive home to work spillover more likely. Clearly, holding numerous identities does not always lead to conflict or strain (Prottas & Hyland, 2011;Thoits, 1983). Do such results indicate that the effects of positive and negative home to work spillover "cancel each other out"?…”
Section: Figurementioning
confidence: 99%